2002
DOI: 10.4315/0362-028x-65.2.274
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Salmonella on Tomatoes Stored at High Relative Humidity, in Soil, and on Tomatoes in Contact with Soil

Abstract: Salmonellosis has been linked to the consumption of several types of raw fruits and vegetables, some of which may have been contaminated with Salmonella before harvesting. The objectives of this study were to investigate water and soil as reservoirs of Salmonella for the contamination of mature green tomato fruits. Salmonella survived for at least 45 days in inoculated moist soil. The population of Salmonella on tomatoes in contact with soil increased by 2.5 log10 CFU per tomato during storage for 4 days at 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(76 citation statements)
references
References 23 publications
4
72
0
Order By: Relevance
“…We used a single strain of Salmonella Montevideo, whereas Guo et al (12) tested a mixture of five serotypes of Salmonella enterica, including the Salmonella Montevideo strain used herein. In the Guo et al (12) study, Salmonella Montevideo was the most resistant strain, which supports the present results. The pathogen behavior could also be influenced by the grade of tomato ripeness (red vs. green); however, Wei et al (26) found that the ripeness of wounded tomatoes had no apparent effect on Salmonella Montevideo populations after 24 h at 25ЊC.…”
Section: Figure 2 Plots Of Mpd As a Function Of Rh At 30њc (A) And 2supporting
confidence: 91%
“…We used a single strain of Salmonella Montevideo, whereas Guo et al (12) tested a mixture of five serotypes of Salmonella enterica, including the Salmonella Montevideo strain used herein. In the Guo et al (12) study, Salmonella Montevideo was the most resistant strain, which supports the present results. The pathogen behavior could also be influenced by the grade of tomato ripeness (red vs. green); however, Wei et al (26) found that the ripeness of wounded tomatoes had no apparent effect on Salmonella Montevideo populations after 24 h at 25ЊC.…”
Section: Figure 2 Plots Of Mpd As a Function Of Rh At 30њc (A) And 2supporting
confidence: 91%
“…A generally high fecal contamination level was also evident from detection of a high level of E. coli organisms (3 to 7 log 10 CFU g Ϫ1 ) in the paddock compared to the levels after normal application of pig slurry (3 log 10 CFU g Ϫ1 soil) (15). Other studies have reported recovery of Salmonella from soil several months after inoculation, most likely due to different experimental conditions and higher inoculation doses, e.g., 5 log CFU g Ϫ1 (22,28,38,39). E. coli has been reported to a have a survival rate similar to Salmonella, thus providing a good indicator of decimation of Salmonella (38,41).…”
Section: Discussionmentioning
confidence: 91%
“…This concern is directed to Salmonella spp. (24,27,40,47,49) and E. coli O157:H7, because cattle is its main reservoir, explaining the risk of transmission by manure (22,34,43,50).…”
Section: Discussionmentioning
confidence: 99%